A brief outlook into waqf / Dahlia Ibrahim ... [et al.] - Ibrahim, Dahlia; Mohamed Isa, Zuraidah; Ali, Norhidayah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
The word ‘waqf’ comes from the Arabic word ‘waqafa’. It merely means to stop, halt or freeze where the creation of waqf takes away the control of the original owner of his/her property. As such, a physical object proclaimed as waqf is retained or preserved where only the benefit from it can be used to help the needy. The waqfconcept existed long before the emergence of Islam as proven by the establishment of mosques and religious using the donations from the society. It was not known as waqf then but the in tention of the donation is to benefit many people. In short, waqf is a mechanism to improve the quality of life of the society ranging from religious aspects, reduction of poverty, education and health.